Keratocystic odontogenic tumor related to nevoid basal cell carcinoma syndrome: clinicopathological study - Luana Eschholz Bomfin; Ana Paula M. Vivas; Andre Caroli Rocha; Maria Isabel W. Achatz; Clovis Antonio L. Pinto; Fabio Abreu Alves (Universidade Estadual de Campinas, 2015)
Aim: To assess clinicopathological features of patients with keratocystic odontogenic tumor (KCOT) associated with nevoid basal cell carcinoma syndrome (NBCCS) in a single Brazilian institution. Methods: After histopathological analyses of KCOT related to NBCCS, the medical charts of 14 patients were assessed. These patients presented a total of 31 primary and 8 recurrent KCOT. Results: Out of 14 patients, 8 presented a single KCOT, 4 showed synchronous tumors, 1 had 3 metachronous lesions and another patient had 2 synchronous lesions at initial evaluation and then developed other 3 metachronous lesions. Besides the 31 primary KCOTs, 18 lesions were located in mandible and 13 in maxilla. Most tumors presented unilocular pattern and association with a tooth. Conclusions: KCOT is a frequent manifestation of NBCCS and can be its first sign, mainly in young patients. In contrast to a previously published series, most patients presented a single lesion.